2015
DOI: 10.1007/s00429-015-1095-7
|View full text |Cite
|
Sign up to set email alerts
|

Modifications of perineuronal nets and remodelling of excitatory and inhibitory afferents during vestibular compensation in the adult mouse

Abstract: Perineuronal nets (PNNs) are aggregates of extracellular matrix molecules surrounding several types of neurons in the adult CNS, which contribute to stabilising neuronal connections. Interestingly, a reduction of PNN number and staining intensity has been observed in conditions associated with plasticity in the adult brain. However, it is not known whether spontaneous PNN changes are functional to plasticity and repair after injury. To address this issue, we investigated PNN expression in the vestibular nuclei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 90 publications
2
17
0
Order By: Relevance
“…Expression of PNNs in the brain, including the DCN, has been previously shown to be reduced following enriched environmental stimulation (32, 50), locomotion training (51), injury (47,52,53), or drug exposure (54)(55)(56). Our study shows a change in PNN expression during learning of new associations.…”
Section: Discussionsupporting
confidence: 59%
“…Expression of PNNs in the brain, including the DCN, has been previously shown to be reduced following enriched environmental stimulation (32, 50), locomotion training (51), injury (47,52,53), or drug exposure (54)(55)(56). Our study shows a change in PNN expression during learning of new associations.…”
Section: Discussionsupporting
confidence: 59%
“…In addition, creation of PNNs seems to be directly involved in closing the critical period in barrel cortex (McRae et al, 2007; Nowicka et al, 2009). Furthermore, damage to the peripheral vestibular labyrinth of adult rats causes PNN reduction in the lateral vestibular nuclei of the brainstem in conjunction with remodeling of afferents, followed by restoration of PNNs when vestibular compensation is complete (Faralli et al, 2016). In that study it was shown that PNNs break down over the first 3 to 6 days, and have recovered significantly by day 12 and completely by day 24 (Faralli et al, 2016).…”
Section: Hyaluronanmentioning
confidence: 99%
“…Breakdown of nets produces unwanted sprouting of synapses and changes in the balance of excitatory and inhibitory neuronal transmission. For instance, parallel plastic changes of excitatory and inhibitory synaptic transporters of vesicular glutamergic transporter 1 (VGLUT1), VGLUT2 and vesicular GABAergic transporter (VGAT), as well as changes in PNN densities, were observed during vestibular compensation 9 .…”
Section: Introductionmentioning
confidence: 99%